El desarrollo y dominio de las competencias cientifico – profesionales del docente universitario - Rivadeneira Rodríguez, Elmina Matilde (2015)
Knowledge Society requires the intellectually independent professional UN decide for itself, independently, s responsibility, empathy, using self-knowledge m managed and competencies to critically submit their scientific and academic contributions of argumentada Way, passing Modes Performance and Procedures for lifelong learning (Ausubel, 1986). The Fosters teaching the relationships and interactions between learner and teacher As the organizer, guide, orientador, facilitator, Between learners and all these with society through the process of learning to know (cognitive), DO (cognitive) and Ser (metacognitive), paragraph produce and reproduce culture in its broadest sense and achieve v, based on that the fulfillment of the objectives Developers and significativos. (Rojas 2000.68) That particularly Comment on Level of Higher Education, University Training profesional must be directed towards a thorough understanding of the relationship between science, humanities and technology. You also col Student Technology Place, understanding not only of the Curriculum As Application ES ABSTRACT Science Through the Economic Production Machinery, Equipment, Technology Tools dependence, Como but the result of Development of Thought and creatividad humans in specific times and spaces. The teacher who wants to Learning to Investigate Together With learners, must pay attention to the fact Understand and explain the steps that occur in the process of inquiry. It is feasible to El Paso Prior Learning a Research is being yourself That a person thinks, reflects, On scientific professional work. Change of attitude will develop and master the skills methodological, communicative, Technological epistemológicas, socio-profesionales, didactic teaching in teachers to achieve. A creative and respectful attitude Encourage the UN climate of empathy and equanimity towards different opinions, the defense arguments and theses with OK Questioning, Understanding that different approaches to approach the study of fenómeno, Developing selfconcept in students, UN develop scientific language learners When Hagan That is also intended